Decreased dose requirement of antihypertensive agents with age. (2001)
Hypertension is very prevalent in the elderly and treatment has been shown to be beneficial. However, inappropriate doses of drugs may impair the quality of life in this group of patients. In an attempt to assess the role of advancing age on therapy and doses of antihypertensives, the authors studied the antihypertensive dose/response pattern as hypertensive subjects on regular treatment move from the young to the elderly age group. Forty-nine hypertensives who were still being followed up at the medical outpatient clinic. University College Hospital, Ibadan were recruited into the study. The patients were extensively inter viewed and information relating to age, sex, year, age of diagnosis, as well as blood pressure at diagnosis, 6 months and 5 years of therapy were noted. There were HI males and 39 females with mean ages of 66.5 ± 6.6 and 64.5 ± 4.5 years respectively. The mean ages at diagnosis for both male and female groups were 52 ± 9.3 and 50 ± 7.5 years respectively. At diagnosis, 22 (44.8%) patients were started on single (antihypertensive) drug therapy, 23 (46.9%) on two drags while 4 (8.3%) were on 3 drugs. By 5 years of fairly consistent therapy, there were 33 (67.3%) patients on single drug and 16 (32.7%) patients on 2 drugs. No patient was on 3 drugs regimen. The mean blood pressure at diagnosis of 174 ± 24/105 ± 9 mmHg dropped significantly and was maintained at 6 months of therapy at (139 ± 20 / 87 ± 13 mmHg) p < 0.001. After 5 years of therapy the mean was (139 ±24/81 ±8 mmHg) inspite of dose reduction in these patients (p < 0.001). The authors concluded that, in a hypertensive patient who is un regular treatment, consistent and gradual reduction of antihypertensive doses may be carried out with blood pressure remaining within acceptable limits as the patient grows old.